Between Theology and Poverty in the Malay Community in Deli Serdang - Ning Ratna Sinta Dewi (Program Doktor Akidah dan Filsafat Islam, 2019)
The background of this writing departs from the Malays' life, who always identified with poverty, ignorance, and backwardness. Yet history has noted that the value of the Malay tribe in Indonesia. The gentle language, the customs are majestic and coupled with the use of Malay Arabic script in every educational institution in several regions in Indonesia. This makes the Malay people as the pride of the Indonesian nation. In contrast to the current situation, the Malay people live in poverty and stay away from the city's civilization. Coastal is the residential area of the Malay tribes in North Sumatra, especially the Malay tribe in Deli Serdang Regency. This location is a place of research because it is a coastal region where the majority of the population is ethnic Malay. The purpose of this study is to find out how the understanding of the Malay community on the issue of poverty and the correlation of theology.